Peranan Pemerintah Desa dalam Meningkatkan Penerimaan Pajak Bumi dan Bangunan di Desa Pagaran Lambung III Kabupaten Tapanuli Utara - Sipahutar, Netrianni; Wulandari, Novita; Lubis, Yurial Arief (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
The low land and building tax receipts in Pagaran Lambung III village need to be strengthened by the role of the village government in this case apparatus and institutional resources. This study aims to identify and describe the role of the village government in increasing land and building tax revenues. Through the role of a good village government and complete village head office facilities, which can support the administration of tax payments, it can increase land and building tax revenue and community participation in Pagaran Lambung III village, which is one of the sources of local revenue (PAD) of North Tapanuli district. The inhibiting factors are the low level of the people's economy, the low level of public tax knowledge and the payment system which is still manual. In solving the problems that occur researchers use the role theory put forward by Ryaas Rasyid. This type of research uses a qualitative approach descriptive method. Data sources were collected based on data collection techniques, namely observation, interviews and documentation. As a reinforcement of this study, it consisted of key informants, main informants and additional informants. The research results obtained are that the role of the village government has not optimally carried out its functions and obligations in providing guidance or direction in solving land and building tax revenue problems that have not reached the tax realization target set by the North Tapanuli district government.